Perlindungan Hukum Rekam Medis elektronik dalam Praktik Kedokteran Gigi: Legal Protection of Electronic Medical Records in Dental Practice - Darmadi, Eveline Yulia; Ropii, Imam; Agus Susanto, Dany (Jurnal Hukum dan Etika Kesehatan, 2026)
The implementation of electronic medical records in dental practice raises legal issues that extend beyond administrative concerns to include the protection of patient rights and legal certainty for dental professionals. The enactment of Law Number 17 of 2023 on Health strengthens the obligation to adopt digital medical records while simultaneously creating potential normative tensions with personal data protection and technical regulations on medical records. This study aims to analyze the legal protection of electronic medical records in dental practice and to identify normative gaps that may weaken legal protection for both patients and healthcare professionals. This research employs a normative juridical method using statutory and conceptual approaches by examining health legislation, personal data protection law, and relevant implementing regulations. The findings indicate that electronic medical records occupy a strategic position as both clinical documentation and legal evidence; however, the existing regulatory framework has not yet ensured proportional legal certainty. Ambiguities in the allocation of legal responsibility, potential normative disharmony, and the absence of specific regulations for dental practice may expose patients and dental professionals to legal risks. Therefore, regulatory strengthening and normative harmonization are required to ensure that the digitalization of medical records effectively safeguards patient rights and professional accountability.